Meningkatkan Nilai Kemanusiaan Dengan Cara Saling Membantu Dalam Kehidupan Bermasyarakat - Nurul Asriari; Rifky Mochamad Fauzan; Risma Aprilia; Salwa Noor Siva Najla; Shasa; Syima Asshofa; Tarisza Fitrhotunnada; Yoga Endang Irawan; Zahra Siti Fatimah; Dian Herdiana (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This activity aims to increase empathy and sympathy for fellow human beings by sharing and helping people who are more in need. Activities are carried out in their respective residential areas for approximately one month, from November 2021 to December 2021. Various activities have been carried out such as: Sharing with others, teaching children around the house, helping each other in the surrounding environment by how to contribute to an activity and event so that it runs smoothly. Sharing with others is given to orphans, people who are affected by disasters, and people who cannot afford it in the form of basic materials, food for people in need and writing utensils for orphanage children. This teaching activity is carried out in various places including in prayer rooms, madrasas and the home environment with methods not only learning but being innovated with games and questions and answers so that the children do not get bored. Assistance activities are carried out by assisting in the activities of the Prophet Muhammad's birthday, helping to clean the prayer room, and assisting PKK and posyandu activities. After holding all these activities, it is hoped that social relations between communities will be strengthened, places of worship and the environment will be cleaner, and the existing children will be of higher quality in every aspect, both knowledge and behavior